Sosialisasi Aspek Psikologis yang harus dimiliki oleh Atlet dan Pelatih Bola voli: Sosialisasi Aspek Psikologis yang harus dimiliki oleh Atlet dan Pelatih Bola voli - Sujarwo Sujarwo (Altruis: Journal of Community Services, 2021)
The purpose of this community service is to provide knowledge to athletes and volleyball coaches about the psychological aspects that volleyball athletes must have and for coaches to be able to train these aspects in training. The community service method is carried out with a participatory educational approach through material presentation and discussion using a website seminar (webinar) using the zoom application. The material given is about the concept of psychological aspects that volleyball athletes must have and how the coach trains them. The indicator of achievement is an increase in the score of knowledge (cognitive) obtained by volleyball athletes. The instrument used was a test item test. The target of this service is non-productive people, namely 3 coaches and 6 athletes in Bantul Regency. The service was carried out on February 4, 2020. Descriptive data analysis, statistical test using the mean difference test. The results of the dedication showed that there was an increase in the mean mean of pre-test 72.22 to 82.22 post-test, an increase of 10%. Athletes' knowledge of this psychological aspect is very important to provide insight to the psychological aspects that they must master, and for the coach to be able to design exercises to develop psychological aspects for the athlete